Oxidative stress–driven metabolic interactions underlying the hepatoprotective effects of a phytocomplex in ethanol-induced liver injury - Rana Jafarova; Sevda Guliyeva; Sevinj Abasova; Nigar Guliyeva; Narmina Jabbarova; Anaxanim Yusifova; Besti Asadova (Journal of Complementary and Integrative Medicine, 2026)
Abstract Objectives This study aimed to investigate the interactions between biochemical, oxidative, and morphological markers of liver injury in an experimental model of alcoholic hepatitis and to evaluate the hepatoprotective efficacy of a herbal phytocomplex (AZHEPOFIT) within an integrated mechanistic framework. Methods Alcoholic hepatitis was induced in 40 male rats by oral ethanol administration combined with a high-fat diet for 21 days. From day 22, animals received AZHEPOFIT (1 mL/100 g body weight) daily for 14 days. Biochemical parameters, oxidative stress markers, antioxidant status, lipid profile, and liver histomorphology were assessed. Correlation analysis was performed using Spearman’s coefficient. Results Alcoholic hepatitis was associated with pronounced cytolysis, cholestasis, oxidative stress, dyslipidemia, and marked histopathological alterations, including steatosis, hepatocyte ballooning, inflammation, necrosis, and early fibrosis. AZHEPOFIT administration significantly reduced cytolytic enzyme activity and lipid peroxidation, enhanced antioxidant defense, improved lipid metabolism, and attenuated structural liver damage. Strong correlations exist between oxidative stress markers and cytolytic enzymes, and inverse relationships with antioxidant parameters, indicating a coordinated pathogenic network linking oxidative stress, lipid metabolism, and hepatocellular injury. Conclusions The hepatoprotective effects of AZHEPOFIT are associated with the modulation of interconnected oxidative stress–metabolic pathways. These findings provide mechanistic insight into phytotherapeutic intervention in alcohol-induced liver injury and support targeting redox-dependent pathways as a promising therapeutic strategy.